2020
DOI: 10.1016/j.heliyon.2020.e03603
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cancers diagnosed in Jamhuriyat Hospital, Kabul, Afghanistan

Abstract: Throughout the world, there exists a clear need for the maintenance of cancer statistics, forming an essential part of any rational programme of cancer control, health-care planning, etiological research, primary and secondary prevention, benefiting both individuals and society. The present work reports only on the prevalence of cancers in the Oncology Department of Jamhuriyat Hospital, Kabul, Afghanistan following several decades of war. Materials and methods: A quantitative retrospective cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…First, the small sample size increased greatly the uncertainty around the estimated proportions of women with delays in healthcare seeking and diagnosis. Non-etheless, even with the measured uncertainty, patient delay was observed for at least 59% of CC patients, and the overall low numbers of CC patients identified through clinical files are consistent with previous literature on cancer diagnoses in Kabul hospitals (37). Second, it was beyond the scope of the present study to investigate the factors beyond healthcare delays: the women reported the recommendations received from the clinicians, but the later could not be interviewed with regard to their workload or knowledge.…”
Section: Strengths and Weaknessessupporting
confidence: 88%
“…First, the small sample size increased greatly the uncertainty around the estimated proportions of women with delays in healthcare seeking and diagnosis. Non-etheless, even with the measured uncertainty, patient delay was observed for at least 59% of CC patients, and the overall low numbers of CC patients identified through clinical files are consistent with previous literature on cancer diagnoses in Kabul hospitals (37). Second, it was beyond the scope of the present study to investigate the factors beyond healthcare delays: the women reported the recommendations received from the clinicians, but the later could not be interviewed with regard to their workload or knowledge.…”
Section: Strengths and Weaknessessupporting
confidence: 88%
“…Some progress has been made, but there are still many hurdles, including a shortage of experienced doctors and medical staff, especially in rural areas where 74% of the population lives. In these areas, patients suffer from poor hygiene, poor transport facilities to health centres and limited medical knowledge in self-assessment [ 3 6 ]. There are only sparse data on breast cancer in Afghanistan [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“… 2 In Afghanistan, no nationwide cancer study has ever been conducted to demonstrate the incidence and mortality rate of EC except for a single center study, in which it was estimated that EC was most common cancer in males and the second most common cancer in females. 3 …”
Section: Introductionmentioning
confidence: 99%
“…2 In Afghanistan, no nationwide cancer study has ever been conducted to demonstrate the incidence and mortality rate of EC except for a single center study, in which it was estimated that EC was most common cancer in males and the second most common cancer in females. 3 EC arises from surface lining cells of the esophageal mucosa. There are two main histologic patterns of EC, 1 esophageal squamous cell carcinoma (ESCC) and 2 esophageal adenocarcinoma (EAC).…”
Section: Introductionmentioning
confidence: 99%